Phytochemical Profile and Antibacterial Activity Test of Medicine Plants in Southeast Sulawesi Against Salmonella Typhi YCTC as An Alternative Addition to Substitution Ingredients for Halal Products - Budikafa, Muhammad Jefriyanto; Sahidin; Rini Hamsidi (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Phytochemical profile and antibacterial activity test performed on several medicinal plants methanol extracts of plants Keji beling (Strobilanthes crispus BI), Starfruit (Averrhoa bilimbi Linn.), Kangkung (Ipomoea aquatica), Secang (Caesalpinia sappan Linn.) and Jathropa (Jatropha curcas Linn.) existing in the Southeast Sulawesi. Phytochemical screening carried out by TLC method to identify classes of secondary metabolic compounds like alkaloids, flavonoids, tannins, saponins and triterpenoids, while the antibacterial activity test against the bacteria Salmonella typhi YCTC using the agar diffusion method with chloramphenicol as a positive control. The results obtained show that the extract of the roots and leaves of plants of S. crispus yield a diameter of 9 mm and 5 mm clear zone, the extract of the leaves of plants A. bilimbi yield a diameter of 9 mm clear zone, while the extract of the trunks and flowers of C. sappan. plants produce a clear zone diameter of 3,5 mm and 6 mm against the bacteria. extracts from plant parts that have activity against salmonella bacteria can then be further investigated to obtain compounds that have potential as antibacterial and can be used as alternatives as herbal medicinal ingredients in halal products.